Identifying Electrocardiogram Pattern Changes and Their Association with Echocardiography among Malaysian Footballers Attending Pre- Participation Evaluation / Farnaza Ariffin ... [et al.] - Ariffin, Farnaza; Khir, Rizmy Najme; Mohamed-Yassin, M; Baharudin, Noorhida; Ismail, Ilham Ameera; Abdul-Hamid, Hasidah; Abd-Halim, Haizlene (Universiti Teknologi MARA Cawangan Selangor, 2020)
Introduction: Sudden cardiac death is the most common medical cause of death in athletes. The aim of this study was to identify the electrocardiogram (ECG) pattern changes and its association with echocardiography among Malaysian footballers during a pre-participation evaluation (PPE). Methods: A retrospective study was conducted on footballers attending a PPE at a primary care centre. Secondary data collection was conducted and the proforma included clinical history, physical examination, ECG, Echocardiogram and cardiovascular risk factors assessment such as heart rate, blood pressure, lipid profile, fasting blood sugar and creatinine. Data were extracted from the medical records, echocardiogram report and the original ECG. The ECG patterns were analysed according to the International consensus for ECG interpretation in athletes to determine physiological versus pathological changes. The data was analysed using SPSS v24. Results: This study included 85 male Malaysian footballers with a mean age of 20.1 ± 3.0 years. The mean resting heart rate was 55.2 ± 9.3 beats per minute. Abnormal ECG changes were found in 20% of the participants, which were higher compared to that reported in other studies (14% - 17.3%). The normal ECG findings in athletes were sinus bradycardia (76.5%), J-point elevation (68.2%), prolonged PR interval (3.5%) and incomplete right bundle branch block (4.7%). The abnormal ECG changes were multiple T wave inversions (5.9%), hypertrophy (2.4%), and deep Q-waves (8.2%). Four abnormal ECGs were consistent with abnormal echocardiography findings and out of these, two ECGs with hypertrophic changes were consistent with mild inter atrial septal bulging and apical hypertrophy. Conclusions: Malaysian footballers have ECG changes that are consistent with physiological changes in athlete's heart. The positive association between ECG and Echocardiogram findings are useful in confirming pathological ECG changes. Physicians should be trained in PPE protocol and ECG interpretation in athletes in order to improve identification of those at risk of sudden cardiac death.